2009
DOI: 10.1002/smll.200801593
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode Arrays for Electrochemistry: Approaches to Fabrication

Abstract: Microelectrode arrays have unique electrochemical properties such as small capacitive-charging currents, reduced iR drop, and steady-state diffusion currents. These properties enable the use of microelectrode arrays and have captured much interest in the field of electrochemistry. Techniques for the fabrication of such arrays are reviewed. The relative features and merits of different techniques are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
159
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(161 citation statements)
references
References 167 publications
(246 reference statements)
1
159
0
1
Order By: Relevance
“…Cyclic voltammograms at 0.005 V s ( Fig. 1B) revealed the microelectrode behavior as presented in other studies (Choudhry et al, 2010a;Huang et al, 2009;Kadara et al, 2009b). Increasing the spray time had a significant reduction effect on the peak intensity and the peak-to-peak separation revealing that the cosmetic spray reduced the amount of accessible graphite ( Figs.…”
Section: Spray Modified Spcesupporting
confidence: 78%
“…Cyclic voltammograms at 0.005 V s ( Fig. 1B) revealed the microelectrode behavior as presented in other studies (Choudhry et al, 2010a;Huang et al, 2009;Kadara et al, 2009b). Increasing the spray time had a significant reduction effect on the peak intensity and the peak-to-peak separation revealing that the cosmetic spray reduced the amount of accessible graphite ( Figs.…”
Section: Spray Modified Spcesupporting
confidence: 78%
“…Microelectrodes have been fabricated using a variety of methods to produce different designs [2][3][4]. Our group has investigated the construction of microband devices which have been fabricated by covering the screen-printed carbon electrode (SPCE) working area with polyvinyl chloride (PVC) insulation tape, then cutting transversely across the centre of the working area [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the different dimension of working gold electrodes, different cyclic voltammograms (CVs) and Nyquist diagrams of EIS were presented. As the electrode dimension reduced, the absolute current decreased while the corresponding resistance increased, which was attributed to the differential mass diffusion profiles 16. After modification with mercapto β‐CD, it can be observed that the electron‐transfer resistance ( R et,mod , semicircle domain in EIS) increased by different degrees in comparison with the 2 mm, 25 μm, and 400 nm diameter bare gold electrode, indicating that mercapto‐β‐CD SAMs had been decorated onto the working electrode surface.…”
Section: Resultsmentioning
confidence: 99%